(3JMaI GdehOhO aj GdebUhQ hGdeeOhOs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3eMeO Hf YHO Gddg GHf GdTeGN Hf YKeGf Hf CMeO Hf CfYe GdjeGfi s)
(3ChdgG (B:s
(3bGd GdTjN HOCJ HMeO Gdg agh SfGA hddfWb efg HgLI hHgGA dg JMaI GdehOhO JSejI abO JCJi HgPG ddeQGO LdGA T (B: (3Gdghi HGdbUQ ghi GdfaS , hHGdeO eUOQ ghi GdTF EPG NdG s
(3BNQgG (B:s
(3ef HGH eG jVe ajbUQ hjeO hGdeYfi hGMO , bhdg (B: (3hGddhHjG HGdbUQ hGdeO MH eYQha , PcQ GdCRgQi bUQg heOg hGSCd di YahkG hfjd LhGQge ZOG aEdi PG SGQY GdSYOGA JeJ hGdMeO ddg s
(3GdfSNI ebGHdI ZjQ eQI aUMJs
(3eTQhMs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
Keywords: (3GddZIs